Fading knowledge of hand-stitched football production - Zaheer, Muhammad; Kausar, Abdul Rashid (The Journal of Humanities & Social Sciences, 2022)
This study highlights the hand-stitched football production by Pakistani artisans, called “stitchers” in the local language. Pakistan fulfils the 70% demand for hand-stitched footballs in the world. With the advent of technology, hand-stitched football production is fading away gradually. This is a qualitative study using grounded theory methodology. Semi-structured interviews of stitchers and managers were conducted at their workplaces. Informants were selected using the purposive sampling technique. It is found that manual football production requires a higher number of human resources, and getting a higher production volume is demanding. Automation is to replace the manual production processes ultimately. Moreover, the knowledge transfer & sharing of manual stitching are fading due to low socio-economic value. The art and knowledge of manual stitching might disappear if not preserved.